Strengthening Islamic Character to Increase Learning Interest, Literacy Skills, and Environmental Concern in Vocational Schools - Novita Sari (GHAITSA : Islamic Education Journal, 2025)
The study aims to analyze the role of strengthening Islamic character in enhancing students’ learning interest, literacy skills, and environmental concern in vocational schools. The research responds to the growing need for character education that integrates Islamic values into the learning process, especially within vocational education contexts that prepare students for both professional competence and moral integrity. Using a mixed-methods approach, data were collected through questionnaires, interviews, and observation involving students and teachers from selected vocational schools in Bengkulu. The findings reveal that implementing Islamic character values—such as discipline, responsibility, honesty, and respect for creation—has a positive impact on students’ motivation to learn and their literacy engagement. Furthermore, the internalization of Islamic ethics fosters greater environmental awareness, reflected in sustainable practices within the school environment. Strengthening Islamic character thus functions not only as a moral foundation but also as a catalyst for academic and social growth. The study suggests that vocational schools should systematically integrate Islamic character education into their curricula and extracurricular programs to nurture holistic learners who are intellectually skilled, morally grounded, and environmentally conscious